Cap d'Encre. - Salle de Nevers, Charleville-Mezieres (Brussel : Cap d'Encre, 1970)
Winance, Alain ; Belgeonne, Gabriel ; Carcan, René ; Cox, Jan ; de Bolle, Francis ; Hendrickx, Jos ; Laffineur, Marc ; Landuyt, Octave ; Lismonde ; Marchoul, Gustave ; Mels, René ; Peire, Luc ; Toussaint, André
biografie
Cap d'Encre, Salle de Nevers, Charleville-Mezieres, 9 au 24 Mai 1970
boek